Formulation and Stability of Cellulose Particles Enriched with Phenolic Acids - Mirela Kopjar; Josipa Vukoja; Ivana Buljeta; Ina Ćorković; Anita Pichler; Josip Šimunović (Polish Journal of Food and Nutrition Sciences)
Dietary fibers and phenolic acids are recognized for their various health benefits; thus, cellulose was selected as a carrier polymer of phenolic acids, including gallic acid and caffeic acid. Dried cellulose particles were prepared through the complexation of different amounts of cellulose (2.5, 5, 7.5 and 10%, w/v) with a constant amount of phenolic acids. Additionally, the complexation time was 15 or 60 min with the goal to determine an impact of the duration of complexation on the adsorption of phenolic acids onto cellulose. The prepared particles were stored at ambient temperature for 12 months to assess their storage stability. Cellulose particles were assessed for the amount of adsorbed phenolic acids and antioxidant activities. For both phenolic acids, the same correlation was established, i.e., reduction of adsorption of phenolic acids occurred with the increase of cellulose amount during complexation. The duration of complexation was not a significant factor in the adsorption of phenolic acids. Antioxidant activity generally followed the trend that was obtained for the amount of adsorbed phenolic acids. Comparing both phenolic acids, cellulose had a higher affinity for caffeic acid (4.665 g/kg) than for gallic acid (3.399 g/kg). However, greater stability of gallic acid/cellulose particles was observed throughout the storage. After storage, the content of gallic acid in cellulose particles slightly decreased (up to 3%), while that of caffeic acid decreased from 10 to 20%. The complexation of phenolic acids with cellulose was proven by recording infrared spectra. Formulated cellulose particles can be a valuable tool for the preparation of plant-based functional additives which can be used for the enrichment of products with phenolic acids in order to improve their antioxidant potential and stability.